2013
DOI: 10.1542/peds.2012-0817
|View full text |Cite
|
Sign up to set email alerts
|

Voice Abnormalities at School Age in Children Born Extremely Preterm

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Isolated case reports of abnormal voice after extremely preterm birth are well described; however, there are no systematic studies of long-term voice outcomes in children born preterm.WHAT THIS STUDY ADDS: Significant voice abnormalities were found in more than half of tested children born before 25 weeks' gestation. Multivariable analyses showed that the number of intubations, not the duration of intubation, and female gender were strongly associated with this adverse outcome. ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Firstly, noninvasive respiratory support may prevent direct complications of a difficult intubation, such as vocal cord dysfunction or subglottic stenosis, which may lead to prolonged ventilation and ventilator-induced lung injury. 50,51 Secondly, the absence of an endotracheal tube may avoid reflex-induced apnea occurring in response to mechanical stimulation of the laryngeal mucosa. 52 Thirdly, noninvasive respiratory support preserves normal laryngeal function, allows normal mucociliary clearance of lung secretions, and may prevent secondary lung damage by reducing the incidence of ventilatorassociated pneumonia.…”
mentioning
confidence: 99%
“…Firstly, noninvasive respiratory support may prevent direct complications of a difficult intubation, such as vocal cord dysfunction or subglottic stenosis, which may lead to prolonged ventilation and ventilator-induced lung injury. 50,51 Secondly, the absence of an endotracheal tube may avoid reflex-induced apnea occurring in response to mechanical stimulation of the laryngeal mucosa. 52 Thirdly, noninvasive respiratory support preserves normal laryngeal function, allows normal mucociliary clearance of lung secretions, and may prevent secondary lung damage by reducing the incidence of ventilatorassociated pneumonia.…”
mentioning
confidence: 99%
“…Thirteen participants were female. Whilst participation in this study was voluntary, the larger number of female participants reflects the higher incidence of dysphonia found in females in this cohort [14]. Variables included were those with a demonstrated link to dysphonia following preterm birth.…”
Section: Resultsmentioning
confidence: 99%
“…Dysphonia has been reported in preterm children, and associated with frequency of intubation, female gender, birth weight, gestational age and emergency intubation [13][14][15]. Dysphonia in adulthood, associated with left vocal cord paralysis following surgical ligation of patent ductus arteriosus in extreme prematurity, has also been documented [13].…”
Section: Introductionmentioning
confidence: 99%
“…Three large-scale observational studies reporting on the incidence of dysphonia in preterm children were identified [18,19,20]. There were no studies reporting treatment or therapy outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…While the study of Røksund et al [19] was limited to a subsection of the extremely preterm population, the studies of Garten et al [20] and French et al [18] had access to the entire cohort of NICU discharges in the respective study centres, so selection bias is unlikely. Common factors associated with dysphonia across those studies were birth at <27 weeks' gestation, birth weight <1,000 g and intubation.…”
Section: Discussionmentioning
confidence: 99%